Validity and reliability of measures of burnout, resilience, leadership and interprofessional relationships in a Frontline Healthcare Workers Crisis Survey (FHWCS) and Healthcare Leaders Crisis Survey (HLCS) - David Besong Tataw; Nana Arthur-Mensah; Sandra Spataro; Deborah Patten; Stephen Robert Poulin; Kinsey Bryant-Lee (Journal of Health Organization and Management, 2026)
Purpose The COVID-19 pandemic challenged and transformed the healthcare workplace and the interconnections between leaders and frontline workers, and interprofessional configurations thus necessitated holistic psychometric studies that encompassed frontline workers and leaders. Within a conceptual framework combining job demands-resources and open systems theories, two studies (2023 and 2025) assessed the validity and reliability of measures of burnout, resilience, leadership behavior, interprofessional relationships, workplace environment and outcomes (turnover, job satisfaction, patient outcomes and performance) for frontline healthcare workers (N = 209) and leaders (N = 101). Design/methodology/approach In study 1 (2023) we assessed validity and tested reliability evidence using exploratory and confirmatory factor analysis (EFA/CFA), convergent validity, discriminant validity, Cronbach's alpha, intercorrelation analysis and composite reliability for burnout and resilience in phase 1. EFA, convergent validity, discriminant validity, Cronbach's alpha and intercorrelation analysis, for interprofessional relationships and leadership behaviors covering frontline healthcare workers in phase 2; and healthcare leaders in phase 3, respectively. In study 2 (2025), we assessed the content and face validity of each question. Findings We established evidence of validity and reliability for measures of burnout and resilience for frontline healthcare workers and leaders, interprofessional practice and perceived leadership behavior scales among frontline workers and interprofessional healthcare practice leadership and managers' leadership behavior scales. Further, content and face validity were confirmed for all constructs. Originality/value Our contributions include the following: a more comprehensive and integrated psychometric toolkit with crisis-assessment utility, the extension of validation work across two healthcare groups and role-specific, validated measures of burnout, resilience and interprofessional practice leadership for healthcare leaders.